"Green cables" – Development, opportunities and legal challenges: Part I. (3rd July 2018) - Agarwala, Nitin
ABSTRACT: Modern submarine cables, known for their applications in telecommunications and connectivity, are currently being explored for possible applications in marine environmental monitoring by virtue of advancements in the integrated sensors and repeaters that can be installed on these cables at a mere additional outlay of 5–10 per cent of the total system deployment cost. These submarine cables are thus providing a sweet alternative for use in marine scientific research and are referred to as 'telecom-marine data cables', 'SMART cables', or simply 'green cables'. However, a few obstacles exist in their usage, as the submarine telecommunication cables have been granted unique rights and freedom by UNCLOS while data gathering through marine scientific research is dependent on national restrictions and has been left undefined in UNCLOS. Since the on-going effort of using these cables for dual use is being progressed without addressing the associated legal-regulatory aspects, there exists a need to revisit the existing legal regime for these emerging green-cables. In this two-part article, while part I will deal with the opportunities for development of 'green cables' part II will deal with the associated legal challenges and possible efforts to address these challenges.